Antioxidant responses and deregulation of epigenetic writers and erasers link oxidative stress and DNA methylation in bovine blastocysts. Issue 12 (7th December 2017) - Bomfim, Monalisa M.; Andrade, Gabriella M.; del Collado, Maite; Sangalli, Juliano R.; Fontes, Patrícia K.; Nogueira, Marcelo F.G.; Meirelles, Flávio V.; da Silveira, Juliano C.; Perecin, Felipe
Abstract : Early mammalian embryos derived from in vitro fertilization are exposed to conditions distinct from the native oviduct‐uterine environment, including atmospheric oxygen that promotes cellular oxidative stress and alters gene expression. High oxygen partial pressure during embryo development is associated with low pregnancy rates and increased embryonic apoptosis. We investigated how bovine embryos responded to high (20%) or low (5%) oxygen partial pressure during in vitro culture, evaluating levels of reactive oxygen species (ROS) as well as changes in the expression of oxidative stress‐ and epigenetic‐related transcripts and miRNAs in blastocysts. Additionally, we determined the global DNA methylation levels in the resulting embryos. Our data indicated that bovine blastocysts produced in vitro under high oxygen partial pressure possessed elevated ROS abundance and exhibited increased expression of CAT, GLRX2, KEAP1, NFR2, PRDX1, PRDX3, SOD1, TXN, and TXNRD1, versus reduced levels of the oxidative stress‐related bta‐miR‐210. These stressed embryos also presented altered expression of the epigenetic‐associated transcripts DNMT3A, H2AFZ, H3F3B, HDAC2, MORF4L2, REST, and PAF1 . In addition, we demonstrated that embryos cultured under high oxygen partial pressure have increased global DNA methylation, suggesting that DNA hypermethylation is mediated by the deregulation of epigenetic‐related enzymes due to oxidative stress.